(untitled) (World Bulletin of Social Sciences, 2025)
Development must be seen as a response to the total context of a given society. This response is determined by some external factors such as the context and by internal factors such as the peoples worldviews. The thought structures, the pattern of the meaning and the basic religious convictions are also influenced by the context. Traditional African culture is deeply religious and the central motive in this culture has been described as the search for unity, harmonious balance and community. Africans who were taken to America brought with them a diverse range of African polytheistic and Muslim religious traditions. These traditions were often syncretized with one another and with Christianity in America such that the diverse American religious traditions that trace their lineage back to their religious traditions played an important role in the struggle for their rights. This article brings into bear how these traditions formed the African experience in the America using the historical methodological tool. It therefore ends by tracing the African perspectives and the way forward